2018
DOI: 10.1021/acs.est.7b05864
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of 4-Nitrocatechol Formed from OH and NO3 Radical-Initiated Reactions of Catechol in Air in the Presence of NOx: Implications for Secondary Organic Aerosol Formation from Biomass Burning

Abstract: Catechol (1,2-benzenediol) is emitted from biomass burning and produced from a reaction of phenol with OH radicals. It has been suggested as an important secondary organic aerosol (SOA) precursor, but the mechanisms of gas-phase oxidation and SOA formation have not been investigated in detail. In this study, catechol was reacted with OH and NO radicals in the presence of NO in an environmental chamber to simulate daytime and nighttime chemistry. These reactions produced SOA with exceptionally high mass yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
251
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(275 citation statements)
references
References 65 publications
(125 reference statements)
20
251
4
Order By: Relevance
“…Potential breakthrough of such volatile compounds through the SPE filter was probed by collecting smoke samples from a campfire-style burn in Riverside, CA onto a PTFE-SPE-SPE sampling train. Any compounds present on the backup SPE filter were below detection limit despite very high concentrations observed on the front SPE filter, consistent with the negligible breakthrough observed in previous studies using sorbent-impregnated filters (Galarneau et al, 2006) and SPE filters (Tollback et al, 2006). These observations demonstrate the ability of SPE filters to trap relatively volatile compounds, although more work is needed to optimize the recovery and quantification of such compounds.…”
Section: Biomass-burning Samplessupporting
confidence: 87%
See 3 more Smart Citations
“…Potential breakthrough of such volatile compounds through the SPE filter was probed by collecting smoke samples from a campfire-style burn in Riverside, CA onto a PTFE-SPE-SPE sampling train. Any compounds present on the backup SPE filter were below detection limit despite very high concentrations observed on the front SPE filter, consistent with the negligible breakthrough observed in previous studies using sorbent-impregnated filters (Galarneau et al, 2006) and SPE filters (Tollback et al, 2006). These observations demonstrate the ability of SPE filters to trap relatively volatile compounds, although more work is needed to optimize the recovery and quantification of such compounds.…”
Section: Biomass-burning Samplessupporting
confidence: 87%
“…All such compounds were oxygenated and will therefore exhibit very different chemistry and SOA yields than I/SVOCs in vehicular emissions, which have generally been characterized as almost entirely hydrocarbons, particularly alkanes (Tkacik et al, 2012;Zhao et al, 2014Zhao et al, , 2016. Of the identified compounds, only catechol has been studied with respect to gas-phase oxidation and SOA formation (Finewax et al, 2018;Nakao et al, 2011;Yee et al, 2013). Therefore more work is needed to better understand the relative importance of gas-phase vs. heterogeneous reaction pathways for biomass-burning-derived I/SVOCs.…”
Section: Volatility Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iinuma et al (2010), Kelly et al (2010), and Finewax et al (2018) demonstrated their formation through the oxidation of cresol in the presence of NO x . The aerosol formation of nitrocatechols varies between 7 and 65 mg kg −1 for 4-NC, between 0.3 and 6 mg kg −1 for 4M5NC, and between 0.4 and 10 mg kg −1 for 3M5NC.…”
Section: Secondary Compoundsmentioning
confidence: 99%